Prediction of phase equilibrium of the n-butylium acetate-cyclohexane system at low pressures - Pílco Nuñez, Alex (2005)
The group-contribution method of UNIFAC have been evaluated to predict phase equilibria for the n-butyl acetate-cyclohexane system at low pressures. The results show that this method predicts satisfactorily the studied system. The experimental results were obtained in a boiling point apparatus at low pressures, giving in this way experimental data from which we have scarce information.